North and Kubrick between Ligeti and Vaughan Williams for the 2001 Soundtrack - Pinamonti, Paolo (Dipartimento di Scienze per la Qualità della vita (QuVi) - Università di Bologna, 2021)
The story of the missed collaboration between Alex North and Stanley Kubrick for the soundtrack of the film 2001: A Space Odyssey (1968) is faced, in the light of the recently recorded North score for the film. The score highlights not only the too close analogies of North’s various music cues with the temporary tracks chosen by Kubrick but also their original position in the film; film that has suffered until the last many changes. In this research, an aspect that has not been investigated so far has emerged- that of the relationship between North’s music and that of Vaughan Williams, author of the soundtrack for Charles Frend’s film Scott of Antartic (1948). This film curiously has some similarities with Kubrick’s masterpiece, montage of photographic images with special effects, prevalence in the mixing of ‘natural’ noises over music. Furthermore, the analysis of the soundtrack, made from the composer’s point of view, does not want to question the integrity of the filmic text, but, in the light of more recent studies (Platte, 2018), open a plural perspective. Si affronta la vicenda della mancata collaborazione tra North e Kubrick per la colonna sonora del film 2001: A Space Odyssey (1968), alla luce della partitura di North recentemente incisa. Si evidenziano così non solo le troppo strette analogie dei vari music cues di North con le temporary tracks scelte da Kubrick ma anche la loro posizione originaria nel film; film che ha subito sino all’ultimo molti cambiamenti. In tale ricerca è emerso un aspetto poco indagato sinora, quello del rapporto tra la musica di North e quella di Vaughan Williams, autore della colonna sonora per il film di Charles Frend Scott of Antartic (1948). Questo film ha curiosamente alcune analogie con il capolavoro di Kubrick, montaggio di immagini fotografiche con effetti speciali, prevalenza nel mixaggio dei rumori ‘naturali’ sulla musica. Inoltre l’analisi della colonna sonora, fatta dal punto di vista del compositore, non vuole mettere in discussione l’integrità del testo filmico, ma, alla luce di più recenti studi (Platte, 2018), aprire una prospettiva plurale.